1999
DOI: 10.1073/pnas.96.11.6193
|View full text |Cite
|
Sign up to set email alerts
|

Multistep regulation of DNA replication by Cdk phosphorylation of HsCdc6

Abstract: We have characterized HsCdc6, a human protein homologous to the budding yeast Cdc6p that is essential for DNA replication. We show that, unlike Cdc6p, the levels of HsCdc6 protein remain constant throughout the cell cycle in human cells. However, phosphorylation of HsCdc6 is regulated during the cell cycle. HsCdc6 is an excellent substrate for Cdk2 in vitro and is phosphorylated in vivo at three sites (Ser-54, Ser-74, and Ser-106) that are phosphorylated by Cdk2 in vitro, strongly suggesting that HsCdc6 is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
232
4
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(256 citation statements)
references
References 42 publications
17
232
4
3
Order By: Relevance
“…9 Also in our hands exclusive cytosolic localization of Cdc6-YFP during late stages of the cell cycle could as well be reverted into a more nuclear localization when cells were treated with the specific Crm1 inhibitor Leptomycin B (Fig. 2D).…”
Section: Normal Cell Cycle-dependent Regulation Of Recombinant Cdc6-yfpmentioning
confidence: 89%
See 3 more Smart Citations
“…9 Also in our hands exclusive cytosolic localization of Cdc6-YFP during late stages of the cell cycle could as well be reverted into a more nuclear localization when cells were treated with the specific Crm1 inhibitor Leptomycin B (Fig. 2D).…”
Section: Normal Cell Cycle-dependent Regulation Of Recombinant Cdc6-yfpmentioning
confidence: 89%
“…Since this takes place several hours after stimulation, it was concluded that Cdc6 stabilization takes place during S phase. [9][10][11]18 We wanted to test whether this regulation applies to YFP-tagged Cdc6, too. When untransfected HT-1080 cells (Fig.…”
Section: Normal Cell Cycle-dependent Regulation Of Recombinant Cdc6-yfpmentioning
confidence: 99%
See 2 more Smart Citations
“…We have examined expression of the standard proliferation marker Ki67, the DNA replicationlicensing factor Mcm2 and the repressor of origin-licensing Geminin during the proliferative cell cycle, using a novel, nonchemical method for cell synchronisation (membrane elution; Thornton et al, 2002;Helmstetter et al, 2003; Figure 1C). We have employed membrane elution because use of chemical methods for cell synchronisation may account in part for reported discrepancies in temporal periodicities and subcellular localisation of replication proteins such as Orc1 (Pak et al, 1997;Kreitz et al, 2001;Okuno et al, 2001;Li and DePamphilis, 2002) and Cdc6 (Fujita et al, 1999;Jiang et al, 1999;Mendez and Stillman, 2000;Petersen et al, 2000).…”
Section: Cell Cycle Expression Of Origin-licensing Factors and Tumourmentioning
confidence: 99%